Frontotemporal dementia. - Guimarães, Joana (2007)
Frontotemporal dementia (FTD), although less common than Alzheimer's, constitutes a significant percentage of the degenerative dementias, making up 8 to 17% of patients who die with dementia before the age of 70. Several clinical presentations have been described for many authors, which are included in classical behaviour disorder of frontal lobe dementia and in language alterations of progressive aphasias. Classification and diagnosis criteria's of FTP are sometime controversial in literature. So, the authors give an overview of principal's aspects in this area, with focus on clinical, imagiological, patghological and genetic perspective. Furthermore, taken in account this revision was also made a characterization of the patients followed in Dementia Outpatient Clinical Care of our hospital. In these patient characteristics review the follow parameters were analysed: FDT clinical diagnosis; demographics, clinical, imagiological, neuropsychological aspects; and disease evolution. An retrospective study that allowed correlation between some aspects, namely clinical presentation with imagiological and neuropsychological findings. With this revision work, the authors pretend to alert for the relevance of FTD diagnosis, probably misdiagnosticated.